Fibroblast Growth Factor-2 Regulation of Sprouty and NR4A Genes in Bovine Ovarian Granulosa Cells - Jiang, Z. L.; Ripamonte, P. [UNESP]; Buratini, J. [UNESP]; Portela, V. M.; Price, C. A. (Wiley-Blackwell, 2011)
Fibroblast growth factors (FGFs) alter ovarian function, at least in part by inhibiting steroid hormone secretion and affecting survival of granulosa cells. The mechanism of action of FGFs in ovarian follicle cells is largely unknown; in the present study we identified the major pathways used by FGF2 in non-luteinizing granulosa cells cultured under serum-free conditions. FGF2 increased abundance of mRNA encoding SPRY1, 2, and 4, but not SPRY3. Common pathways employed by FGF2 in the regulation of SPRY1, 2, and 4, as demonstrated by immunoblot and inhibitor studies, included ERK1/2 and Akt signaling. In contrast, PKC activation was necessary for FGF2-stimulated expression of SPRY1 and 4, but not for SPRY2. Intracellular calcium flux is critical and sufficient for SPRY2 expression, but not for SPRY1 and 4. We also identified the orphan nuclear receptor NR4A1 as a potential early response gene in FGF2 signaling, whose expression, like that of SPRY2, is critically dependent on calcium signaling. Together, these data identify FGF2-target genes in follicular granulosa cells, and demonstrate alternative pathway use for the differential control of SPRY genes. J. Cell. Physiol. 226: 1820-1827, 2011. (C) 2010 Wiley-Liss, Inc.